A decade of progress on scaling up health and nutrition interventions in India: A countdown to 2030 case study (P04-115-19) - Menon, Purnima; Nguyen, Phuong Hong; Avula, Rasmi; Mani, Sneha; Tran, Lan Mai; Victora, Cesar G. (Oxford University Press, 2019)
India rolled out ambitious program efforts for health and nutrition (H&N) in 2005–06, scaling up community H&N services through the National Rural Health Mission and the Integrated Child Development Services (ICDS). Evidence on the combined reach and impact of these programs on closing equity gaps is limited. We aimed to assess how coverage and equity in interventions have changed between 2006 and 2016.